Ferrothermal reduction of iron(III)phosphate insulating layers in soft magnetic composites. (20th October 2021) - Ouda, K.; Danninger, H.; Gierl-Mayer, C.; Hellein, R.; Müller, A.
ABSTRACT: In modern AC technologies, improving the power efficiency of soft magnetic core materials is a key factor. Powder metallurgy offers a promising alternative for these applications: Soft Magnetic Composites are compacted iron-based powders, each iron particle being electrically insulated from its neighbours by a superficial layer. Accordingly, the thermal stability of the insulating layers used plays an essential role, because the stresses and defects introduced by pressing must be relieved by heat treatment. The thermal stability of FePO4, which is a common insulating barrier, is limited. In the present study, the degrading mechanism was investigated using a mixture of high purity iron powder and FePO4 ·2H2 O. The samples were characterised using a wide variety of analytical methods (DTA/TG, ATR-IR, XRD and XPS). The results show that a ferrothermal reduction takes place, the base material of SMCs – metallic Fe – acting as a reducing agent.